A Low-Dose Combination of Fluvastatin and Valsartan: A New "Drug" and a New Approach for Decreasing the Arterial Age. (3rd March 2015) - Janić, Miodrag; Lunder, Mojca; Šabovič, Mišo
Abstract : We have developed a new "drug" and approach that appear to be effective in reducing arterial age. This "drug" represents a low, subtherapeutic dose of statin and sartan and particularly their low-dose combination. The improvement of arterial wall characteristics, also reflecting in a decrease of arterial age, was achieved after a short period of treatment (one month) with the above-mentioned drugs. In addition, we have also implemented a new, innovative therapeutic approach, consisting of intermittent (cyclic) treatment—alternating short "treatment" periods and much longer "rest" periods (when the beneficial effects are still present but gradually decline). This new "drug" and approach both merit further investigation in order to confirm their antiaging efficacy.